Malay Dance Concept and Its Basic Elements - Dilinar Adlin; Aqsa Mulya; Ruth Hertami; Inggit Prastiawan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The large number of tribes living in North Sumatra causes this area to have a variety of art forms. Starting from the art forms brought by immigrants to the original art forms of North Sumatra, Malay art is one of them. Malay art is the prima donna of art in its native area, it is also one of the most popular art forms in the archipelago, especially its dance forms. Malay dance, like dance in other tribes, becomes a means to express or express how the soul of the people is. Through the presentation of the dance, the characters and customs that apply in the community can be understood. This fact is the reason for researchers to explain how the concepts and basic elements of Malay dance from North Sumatra. This study uses a qualitative approach.